2017
DOI: 10.14740/wjon1000w
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglossal Nerve Mononeuropathy as the First Presenting Symptom of Progressing Multiple Myeloma

Abstract: Multiple myeloma (MM) rarely presents with a primary neurological dysfunction, and if it does it is usually due to a plasmacytoma. This is the first case to discuss hypoglossal nerve dysfunction as the first sign of MM progression secondary to severe pathophysiologic bone lysis. A PubMed-based literature search was completed on April 17, 2016 for the terms “multiple myeloma” and “hypoglossal nerve neuropathy”. A 73-year-old woman with known MM who received little treatment for several years, presented secondar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0
5

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 12 publications
0
3
0
5
Order By: Relevance
“…Isolated CN XII palsy is rare, and about half of the cases are idiopathic [ 5 ]. A prior study indicated cancer, trauma, and ischemia were most commonly associated with isolated CN XII palsy [ 6 ]. The most helpful test would be imaging along the entire course of the nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Isolated CN XII palsy is rare, and about half of the cases are idiopathic [ 5 ]. A prior study indicated cancer, trauma, and ischemia were most commonly associated with isolated CN XII palsy [ 6 ]. The most helpful test would be imaging along the entire course of the nerve.…”
Section: Discussionmentioning
confidence: 99%
“…Schädelbasismetastasen mit Hirnnervendefiziten traten in unserer Analyse überwiegend als Metastasen von Prostatakarzinom, Mammakarzinom oder multiplem Myelom auf. In der Literatur dominieren Fallbeschreibungen von Patienten mit Prostatakarzinom [19,27,28,30] und multiplem Myelom [8,[22][23][24]. Beschreibungen von Patientinnen mit Mammakarzinom sind etwas seltener zu finden [5,6,18,19] Von den ersten neurologischen Symptomen bis zur Therapie vergingen im Mittel knapp 3 Monate.…”
Section: Diskussionunclassified
“…El síndrome del cóndilo occipital consiste en la presencia de dolor en región occipital unilateral, que empeora con la rotación de la cabeza hacia el lado contrario, y paresia del XII par craneal ipsilateral, lo cual genera dificultad para la articulación de palabras y/o dificultad para tragar 1,2,3,4,5,6,7,8,9,10,16,17,19,20 . Se debe al compromiso del conducto del hipogloso por el cual emerge el XII par craneal.…”
Section: Introductionunclassified
“…Se debe al compromiso del conducto del hipogloso por el cual emerge el XII par craneal. Su principal etiología es la enfermedad neoplásica secundaria 3,5,6,7,9,10,19,20) . Las lesiones primarias más comúnmente asociadas son el cáncer de mama y de próstata, seguidos por los tumores colorrectales, renales, nasofaríngeos, óseos primarios y por ultimo linfomas 2,7,8,11,12,13,16,17 .…”
Section: Introductionunclassified
See 1 more Smart Citation